Identification of a Reduction Product of Aristolochic Acid: Implications for the Metabolic Activation of Carcinogenic Aristolochic Acid - Priestap, Horacio A. (2010)
Aristolochic acids are nephrotoxic and carcinogenic natural products that have been implicated both in the endemic nephropathy in the Balkans region and ailments caused by ingestion of herbal remedies. Aristolochic acids are metabolized to active intermediates that bind to DNA. In this study, reduction of aristolochic acid I with zinc/acetic acid afforded a new product which was characterized as 9-methoxy-7-methyl-2H-1,3-oxazolo[5′,4′-10,9]phenanthro[3,4-d]1,3-dioxolane-5-carboxylic acid, designated as aristoxazol, along with the expected aristolactam I. This new compound is a condensation product of aristolochic acid and acetic acid that may be related to the aristolochic acid-DNA-adducts. The proposed mechanism of formation of aristoxazol involves nucleophilic attack of acetic acid on the nitrenium ion of aristolochic acid I. On the basis of these studies a route to the metabolic activation of aristolochic acids and formation of adducts with DNA in in vitro systems is proposed and discussed.